1992
DOI: 10.1016/0735-1097(92)90065-u
|View full text |Cite
|
Sign up to set email alerts
|

Bulboventricular foramen size in infants with double-inlet left ventricle or tricuspid atresia with transposed great arteries: Influence on initial palliative operation and rate of growth

Abstract: Bulboventricular foramen obstruction may complicate the management of patients with single left ventricle. Bulboventricular foramen size was measured in 28 neonates and infants greater than 5 months old and followed up for 2 to 5 years in those patients whose only systemic outflow was through the foramen. The bulboventricular foramen was measured in two planes by two-dimensional echocardiography, its area calculated and indexed to body surface area. One patient died before surgical treatment. The mean initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 15 publications
0
48
0
Order By: Relevance
“…In fact, our study showed that protection of the pulmonary vascular bed, either by native pulmonary or subpulmonary stenosis or a surgically placed PAB, is beneficial to the survival of patients with these congenital heart defects. Although PAB could potentially cause pulmonary artery distortion or pulmonary insufficiency and thus make a future Fontan or DKS procedure more difficult, we and others (17,23,(25)(26)(27) have found that a wellpositioned short-term PAB is generally well tolerated in these patients and does not compromise subsequent surgical palliation or long-term survival.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, our study showed that protection of the pulmonary vascular bed, either by native pulmonary or subpulmonary stenosis or a surgically placed PAB, is beneficial to the survival of patients with these congenital heart defects. Although PAB could potentially cause pulmonary artery distortion or pulmonary insufficiency and thus make a future Fontan or DKS procedure more difficult, we and others (17,23,(25)(26)(27) have found that a wellpositioned short-term PAB is generally well tolerated in these patients and does not compromise subsequent surgical palliation or long-term survival.…”
Section: Discussionmentioning
confidence: 92%
“…This strategy can maintain acceptable anatomy and haemodynamics for later bidirectional Glenn and Fontan procedures [67,68]. However, PAB is implicated in the accelerated development of subaortic obstruction that ultimately jeopardised Fontan candidacy [67][68][69][70][71][72][73][74][75][76]. Other complications associated with a poorly positioned band or migrations are reported, including branch pulmonary stenoses, semilunar valve insufficiency, and erosion with aneurysm formation [67,69].…”
Section: Single Ventriclementioning
confidence: 98%
“…Other complications associated with a poorly positioned band or migrations are reported, including branch pulmonary stenoses, semilunar valve insufficiency, and erosion with aneurysm formation [67,69]. These deleterious effects prompted surgical strategies seeking early initial relief of aortic obstruction with avoidance of PAB [69][70][71][72][73][74][75][76]. A palliative arterial switch operation is advocated for such newborns trading subaortic for neosubpulmonary stenosis [67,77,78].…”
Section: Single Ventriclementioning
confidence: 99%
“…Overall, the relationship between cardiac output and body size is the fundamental driving factor in cardiovascular allometry. heart size; cardiovascular growth; left ventricular volume QUANTITATIVE ASSESSMENT OF cardiac and vascular dimensions is essential to evaluation and management of cardiovascular disorders (5,6,9,42,50,54,68,71,72). Critical to interpretation of these measurements is the establishment of normal standards.…”
mentioning
confidence: 99%